Moderating Effect of Individual Team Member Creativity on the link of Team Diversity & Work Cognition Inventory with Team Performance - Babar, Syeda Urooj; Ahmad, Hafiz Mushtaq; Ahmad, Mubashir (International Review of Management and Marketing, 2020)
This study investigated the impact of team diversity and work cognition inventory on team performance. Quantitative methodological paradigm was selected, following a positivist approach, probability sampling was done in which respondents were picked through simple random sampling and a survey-based questionnaire was used as an instrument for research. The sample was taken from all eleven class-A Combined Military Hospitals (CMH) throughout Pakistan. Individual team member creativity was taken as a moderator between the link of team diversity and work cognition inventory with team performance. Structural equation modeling (SEM) was applied for measuring the effect of the moderator. This study explained employees' individual creativity to significantly moderating team diversity and work cognition inventory link with team performance Thus it aided in understanding diversified teams and taking optimum performance from all members by increasing their social connections and coordination among members and appreciating their individual creativity within the team, so to enhance their satisfaction with the team. Keywords: work cognition inventory, individual team member creativity, structure equation modeling JEL Classifications: M140, Y80 DOI: https://doi.org/10.32479/irmm.10029